Prognostic significance of reduced red blood cell deformability in severe falciparum malaria. - Dondorp, A; Angus, B; Hardeman, MR; Chotivanich, K; Silamut, K; Ruangveerayuth, R; Kager, P; White, N; Vreeken, J (1997)
Severe falciparum malaria is associated with microvascular obstruction resulting from sequestration of erythrocytes containing mature stages of the parasite. Since reduced red blood cell deformability (RBC-D) can contribute to impaired microcirculatory flow, RBC-D was measured in 23 patients with severe falciparum malaria (seven of whom subsequently died), 30 patients with uncomplicated malaria, and 17 healthy controls. The RBC-D, measured by ektacytometry, was significantly reduced in severe malaria and was particularly low in all fatal cases. At a low shear stress of 1.7 Pascal (Pa), a red blood cell elongation index less than 0.21 on admission to the hospital predicted fatal outcome with a sensitivity of 100% (confidence interval [CI] = 59-100%) and a specificity of 88% (CI = 61-98%). The reduction in the RBC-D appeared to result mainly from changes in unparasitized erythrocytes. Reduced deformability of unparasitized red blood cells in severe malaria may contribute to impaired microcirculatory flow and a fatal outcome in severe falciparum malaria.